Children and Digital Media: a dialogue with researchers - Carla Cristiane Loureiro; Rita de Cássia Marchi (Universidade Federal do Rio Grande do Sul, 2021)
The article discusses the relationship of children with digital media, proposing a view, which is not allocated to it on the deterministic and polarized mode in which it has been done. The problem is presented from an unusual angle in the Brazilian literature, shifting from the view of risks to what children actually do with the media. Are in discussion the literature, excerpts of interviews with researcher Dr. Cristina Ponte (coordinator of the Portuguese team of EU Kids Online), and quantitative and qualitative data on the phenomenon. As a result, arises the importance of research done with children themselves in the construction and interpretation of data about their relationships with digital media in different and unequal social and cultural contexts.